Leadership Strategies for Developing a Student Discipline Culture: A Qualitative Case Study Through George R. Terry's POAC Management Framework - Ainun Naim; Ali Rohmat; Dahlia (Journal of Educational Management Research, 2026)
The phenomenon of moral degradation in the contemporary era requires educational institutions to strengthen the value system through systematic leadership management. This study aims to evaluate the leadership strategy of the head of the boarding school in constructing a culture of student discipline at the API ASRI 2 Bandongan Islamic Boarding School using the theory of the management function of POAC (Planning, Organizing, Actuating, Controlling) from George R. Terry. The research method applied is qualitative with an explanatory case study design. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using the interactive model Miles, Huberman, and Saldaña using purposive sampling techniques. The findings of the study revealed that the internalization of discipline culture is carried out through four stages: participatory planning based on traditional values, structured division of tasks to avoid overlapping authority, implementation through leadership example (uswah hasanah) and persuasive communication, as well as digital supervision accompanied by educational sanctions. In conclusion, the success of the formation of discipline in Islamic boarding schools does not rely enough on rigid legal-formal rules, but requires synergy between exemplary leadership figures, orderly organization, and communication that humanizes human beings in applying fair and transparent sanctions.